Stochastic frontier model for cost and profit efficiency of Islamic online banks - Baten, Md Azizul; Begum, Shakera (ARRAY Development, 2014)
Are Islamic online banks stable and efficient? This paper addresses this question.Parametric technique, Stochastic Frontier Analysis is used to evaluate and compare the cost and profit efficiency of the Islamic banks in Bangladesh over the period of 2001- 2010.The specification of functional forms of Translog stochastic cost and profit frontier models are developed.Translog stochastic cost and profit frontier models were found preferable than Cobb-Douglas production function.In case of cost model, other earning assets are found negative but significant and price of labor is observed positive and significant.On the other hand, price of fund with the value of (-0.421) is found significant and negative for profit model, suggest that bank can control more personnel expenses than depositor profit expenses. The year-wise average cost inefficiency and profit efficiency were observed 43.9% and 82% respectively.IBBL was recorded as the most profit efficient bank and ICB limited bank was observed as the most cost inefficient bank.IBBL, Al-Arafah and EXIM banks were more stable in terms of cost efficient than other Islamic banks.